The gold-borrowing market: recent developments - Cox, Ian.; World Gold Council (London: The World Gold Council, 1996)
This study provides an overview of developments which have taken place in the gold-borrowing market during the past three years. The evolution of the market itself, and the underlying forces which led to its rapid expansion, have already been described in detail in this study which provides a reference point for an updated assessment of the changes and events which have shaped the more recent course of the market.
ne 4/04/2018
Loans
Keywords: Borrowing; Gold